2018
DOI: 10.1002/chem.201802038
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent Sequence Selectivity and Diastereoselectivity in the Alkylation of DNA by Decarbamoylmitomycin C

Abstract: Mitomycin C (MC), an antitumor drug, and decarbamoylmitomycin C (DMC), a derivative of MC, alkylate DNA and form deoxyguanosine monoadducts and interstrand crosslinks (ICLs). Interestingly, in mammalian culture cells, MC forms primarily deoxyguanosine adducts with a 1"-R stereochemistry at the guanine-mitosene bond (1"-α) whereas DMC forms mainly adducts with a 1"-S stereochemistry (1"-β). The molecular basis for the stereochemical configuration exhibited by DMC has been investigated using biomimetic synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 52 publications
4
20
1
Order By: Relevance
“…In our previous work, we found that the structure of the nucleobases flanking the target sequence influences both alkylation yields and the ratio of diastereomeric monoadducts . In order to fine tune conditions that favor the formation of 1“‐β adducts, we further investigated this effect by comparing the frequency of 2 b and 2 a in 5′‐AGCT; 5′‐TGCA and 5′‐AGCA sequence contexts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we found that the structure of the nucleobases flanking the target sequence influences both alkylation yields and the ratio of diastereomeric monoadducts . In order to fine tune conditions that favor the formation of 1“‐β adducts, we further investigated this effect by comparing the frequency of 2 b and 2 a in 5′‐AGCT; 5′‐TGCA and 5′‐AGCA sequence contexts.…”
Section: Resultsmentioning
confidence: 99%
“…In order to fine tune conditions that favor the formation of 1“‐β adducts, we further investigated this effect by comparing the frequency of 2 b and 2 a in 5′‐AGCT; 5′‐TGCA and 5′‐AGCA sequence contexts. Duplex oligonucleotides were reacted with fully reduced DMC according to a protocol described previously . Alkylated oligonucleotides were digested by nucleases and phosphatases to the individual nucleosides and the adducted nucleosides ( 2 a and 2 b ) were identified by their UV spectra, their retention time and co‐elution with synthetically prepared standards to confirm their identity .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations